Ethical Considerations for Teacher-Education Researchers of Coteaching - Ritchie, Stephen M. (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2006)
In small-scale studies of coteaching, there are few genuine ethical dilemmas for researchers providing participants are engaged in ongoing dialogue about the purposes and emerging results of the research. When studies are up-scaled for teacher education programs, the territory is uncharted. This adds uncertainty about the ethical codes of practice for a teacher education program director who initiates such research. If the research is likely to lead to valued learning experiences for participating interns without harm to other participants, it may be ethical to proceed. In this paper I suggest that even though getting the balance right will continue to challenge researchers, it will be essential to establish and maintain dialogue between all participants.URN: urn:nbn:de:0114-fqs0604218